Answer:
First of all the rate of change is -2, so the answer would be y = x - 2
(2y² + 7y + 11) - (8y² - 5y + 7) you can distribute the negative sign to the second expression and then combine the like terms
new expression: (2y² + 7y + 11) (-8y² + 5y - 7)
2y² and -8y² equals -6y²
7y and 5y equals 12y
11 and -7 equals 4
The answer is -6y² + 12y + 4
Answer:
rectangle
kite
Step-by-step explanation:
<span>A student was asked to use the formula for the perimeter of a rectangle, p = 2l 2w, to solve for l. the student came up with an answer, p -2w=2l. what</span>
Answer:
Results are below.
Step-by-step explanation:
<u>First, we need to calculate the variable income per job:</u>
<u />
First job= 450 - 150= 300
Second job= 675 - 150= 525
<u>Now, the hourly rate:</u>
<u></u>
Hourly rate= total variable income / number of hours
First job= 300 / 4= $75
Second job= 525 / 3= $175
It is probably that the second job was 7 hours long. If not, he doesn't charge the same amount per hour